Open source data warehousing and business intelligence - Bulusu, Lakshman (Boca Raton, Florida : CRC Press, 2013)
Open Source Date Warehousing and Business Intelligence is an all-in-one reference for developing open source based data warehousing (DW) and business intelligence (BI) solutions that are business-centric, cross-customer viable, cross-functional, cross-technology based, and enterprise-wide. Considering the entire lifecycle of an open source DW & BI implementation, its comprehensive coverage spans form basic concepts all the way through to customization. Highlighting the key differences between open source and vendor DW and BI technologies, the book identifies end-to-end solutions that are scalable, high performance, and stable. It illustrates the practical aspects of implementing and using open source DW and BI technologies to supply you with valuable on-the-project experience that can help you improve implantation and productivity. Emphasizing analysis, design, and programming, the text explains best-fit solutions as well as how to maximize ROI. Coverage includes data warehouse design, real-time processing, data integration, presentation services, and real-time reporting. With a focus on real-world applications, the author devotes an entire section to powerful implementation best practices that can help you build customer confidence while saving valuable time, effort, and resources
1. Introduction -- 2. Data warehousing and business intelligence : an open source solution -- 3. Open source DW & BI : successful players and products -- 4. Analysis, evaluation and selection -- 5. Design and architecture : technologies and methodologies by dissection -- 6. Operational BI and open source -- 7. Development and deployment -- 8. Best practices for data management -- 9. Best practices for application management -- 10. Best practices beyond reporting : driving business value -- 11. EDW/BI development frameworks -- 12. Best practices for optimization -- 13. Open standards for open source : an EDW/BI outlook
Includes bibliographical references and index
Keywords: Business intelligence